Tingkat Persepsi Wisatawan terhadap Agrowisata Kebun Durian Sangiang Bedil - Effendi, Akmal Naufal; Pardani, Cecep; Hardiyanto, Tito (Ma'soem University, 2025)
The Sangiang Bedil Durian Garden, located in Cipeuteuy Village, Darmaraja District, Sumedang, is an attractive agro-tourism destination. This study aims to identify the characteristics and perceptions of tourists visiting the site. Using a descriptive quantitative method through observation and incidental questionnaires administered to 50 respondents, the findings show that the majority of visitors are female, aged 20–29 years, high school graduates, students, earning less than Rp1,000,000, originating from Sumedang, and learned about the site through social media. Most visitors came with friends or family using private vehicles and had a recreational budget under Rp200,000. Although most were first-time visitors, many expressed a willingness to return. Overall, tourist perception was categorized as high, with a total index score of 38.59. The highest-rated aspects were the durian products (41.35), followed by facilities (41.08), attractions (40.90), and supporting services (39.55). However, accessibility received the lowest rating (30.05), due to poor internet connectivity and a less strategic location.